The effect of subtalar joint axis location on muscle moment arms - Zuppke, J. N.; Bennett, H. J.; Ringleb, S. I. (Journal of Biomechanics, 2023)
Most dynamic musculoskeletal models define the subtalar joint (STJ) as a one degree of freedom (DOF) hinge with a tri-planar axis. The orientation of this axis of rotation is often determined as a combination of inclination and deviation angles measured from the ground and midline of the foot, respectively. In defining the location of the axis, often the origin is found at the distal aspect of the heel instead of at the articulation of the talus and calcaneus. Key musculoskeletal modeling definitions, such as muscle moment arms, are dependent on the distance and relative location of muscle insertion to the axis of rotation. Since the axis orientation and origin location affect calculations of muscle moment arm and joint dynamics, there is much need for accurate characterization of the STJ axis to understand the STJ`s role in dynamic weight-bearing motion. The purpose of this study is to explore how the STJ origin location and axis orientation affect muscle moment arms surrounding the ankle. Datasets from the Grand Knee Challenge, posted on the open-source SimTK website, were modeled using OpenSim. Modifying the location of the STJ axis from the original location closer to the articulation between the talus and calcaneus resulted in significant differences in STJ muscle moment arms and peak STJ moments. The findings of this study conclude that the location of the STJ axis origin needs to be considered and accurately defined, especially if the inclination/deviation angles of the rotational axis will be modified to represent a more subject-specific definition.